Microbial succession during the spontaneous fermentation of cocoa in productive units (2021)
Cocoa fermentation is determined by the growth of successions of diverse microbial groups that vary from one region to another. In the present study, a characterization of the samples taken from fermentations of productive units of Valle del Cauca was carried out, to which the concentration of yeasts, lactic acid bacteria, acetic acid bacteria and mesophilic aerobes was measured during 5 days. Additionally, the concentration of reducing sugars and pH of both the cotyledon and the mucilaginous testa were determined. At the end of fermentation, the degree of fermentation was determined (cut-off test and fermentation index). Yeast, acetic acid bacteria and lactic acid bacteria growth was constant during the 5 days of fermentation evaluated, with the exception of M1, which showed a decline in BAA concentration. Average fermentation temperatures of 26, 27 and 25 °C, sugar consumption of 64.40, 88.78 and 98.27% were presented for sampling points 1, 2 and 3, respectively. Knowing the behavior of the microbial groups and their biochemical responses allows understanding the relationships between the growth of the cocoa microbiota and its final quality, which in the future will allow improving the quality of the derived products.